Secondary Angio-Embolization After Emergent Pelvic Stabilization and Pelvic Packing Is a Safe Option for Patients With Persistent Hemorrhage From Unstable Pelvic Ring Injuries - Lustenberger, Thomas; Störmann, Philipp; Eichler, Kathrin; Nau, Christoph; Janko, Maren; Marzi, Ingo (Frontiers in Surgery, 2020)
Introduction: In patients with severe pelvic ring injuries, exsanguination still is the leading cause of death in the early post-injury phase. While mechanical pelvic ring stabilization and pre-peritoneal pelvic packing are mainly addressing venous bleeding, angio-embolization aims to control arterial bleeding. The goal of the present study was to evaluate the rate of postoperative angio-embolization after mechanical pelvic ring injury stabilization and pre-peritoneal pelvic packing. Bleeding sources detected in the angiography and the patient's outcome were investigated. Patients and Methods: Retrospective observational cohort study at a single academic level I trauma center, reviewing all patients with pelvic ring injuries admitted from 01/2010 to 12/2019. Patients with emergent mechanical pelvic ring stabilization (supraacetabular external fixator and/or pelvic C-clamp) and direct pre-peritoneal pelvic packing were further analyzed. Patients that underwent postoperative angio-embolization were compared with those that did not. All postoperative angio-embolizations were evaluated with regards to bleeding sources and type of embolization. Results: During the study period, a total of 39 patients required immediate mechanical pelvic stabilization and direct pre-peritoneal pelvic packing. Of these, 12 patients (30.8%) underwent a postoperative angio-embolization. The following vessels were identified as bleeding sources: superior gluteal artery (n = 6), obturator artery (n = 2), internal pudendal artery (n = 2), unnamed branches of the internal iliac artery (n = 3). A selective embolization was successful in 11 patients; in 1 patient, an unilateral complete occlusion of the internal iliac artery was performed to control the bleeding. Mean time from hospital admission to the surgical procedure was 52.8 ± 14.7 min and the mean time from admission to angio-embolization was 189.1 ± 55.5 min. The in-hospital mortality rate of patients with angio-embolization was 25.0% (n = 3). Of these, 2 patients died due to multiple organ failure and 1 patient due to severe head injury. Conclusion: Secondary angio-embolization after external pelvic fixation and pre-peritoneal pelvic packing was effective in controlling ongoing bleeding. The most frequently detected bleeding vessel was the superior gluteal artery, which is difficult to surgically address, further highlighting the importance of angio-embolization in the management algorithm.